BPJS Claims Pending Case Coding Training at AISYIYAH PADANG RSU: Pelatihan Pengodean Kasus Pending Klaim Bpjs Di RSU AISYIYAH PADANG - Sayati Mandia (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Hospital health facilities are required to complete BPJS claim documents before submitting them to BPJS Health to get reimbursement for treatment costs according to the Indonesian Case Base Groups (INA-CBG's) rates. The BPJS claim process already uses the INA-CBGs program. With this payment method, the accuracy of clinical and procedure code data determines the financing of health services. Service of Community Activities (PKM) aim to provide education regarding ICD-10 coding regulations in minimizing cases of pending claims that occur at Aisyiyah General Hospital, Padang. This PKM did at Aisyiyah Hospital Padang on 06-07 October 2022 Service of Community in the form of outreach regarding the urgency of using the ICD-10 then followed up in the form of practicing ICD-10 coding cases of pending claims to partners. This activity was attended by 18 participants from the medical team and case-mix. Result of pre-test and post-test showed, increasing the team's understanding of ICD-10 coding regulations and cases pending claims.